λ-integrase mediated seamless vector transgenesis platform - Roy, Suki (Nanyang Technological University, 2020)
Genome engineering is an important component of gene/cell therapy and molecular medicine. In this respect, several DNA editing tools, such as ZFNs, TALEN and CRISPR-Cas system are being currently used for transgenesis. However, issues like insertional mutagenesis, off-target events, and small payload size have affected their usage as precise genome editing tools. A novel λ-Integrase based tool was recently developed in the laboratory of Professor Peter Dröge, where a λ-integrase variant could catalyze conservative site-specific integration of the large payload into a safe harbor site(s) of the human genome. The identified safe harbor site(s), termed attH4X, is present within human Long INterspersed Elements-1 (LINE-1) in about 1000 copies dispersed throughout the human genome (Chandra et al. 2016). One of the major requirements of this tool is a circular target vector for Int-mediated recombination into genomic attH4X for which the traditional Escherichia coli is used to produce a plasmid that carries attP4X. This requires the inclusion of bacterial backbone along with payload in the target vector construct that also get inserted into the human genome. However, the presence of bacterial sequences in the conventional plasmid reduces its overall efficiency by increasing its size, silencing transgene expression and activating immune responses in the host cell. Thus, to overcome these limitations and further to improve the safety and targeting efficiency of this tool, the λ-Integrase platform was utilized to eliminate such bacterial sequences by seamless vector generation via in vitro intramolecular recombination. For this, a λ-integrase variant protein was partially purified and a protocol for in vitro seamless vector generation was established. Additionally, to refine and scale up the production of seamless vector, an in vivo platform was developed using E. coli strain LZ41 that can produce a high amount of the seamless vector. λ-Int mediated seamless vector transgenesis into human LINE-1 element has been successfully validated in HT1080 cells and human embryonic stem cells. The switch from plasmid to seamless vector for λ-Int mediated site-specific genomic integration drastically increased the targeting efficiency and reduced off-target events. Furthermore, the seamless vector was utilized for successful transgenesis and expression of therapeutic protein like anti-CD19 chimeric antigen receptor (CAR) in human embryonic stem cells (hESCs). The targeted hES clone showed stable long-term expression of the therapeutic anti-CD19 CAR protein, demonstrating the potential utility of λ-integrase mediated seamless vector transgenesis platform in therapeutic application. Moreover, certain LINE-1 loci were identified as preferred insertion sites for Int-mediated seamless vector transgenesis. DNA sequence logo on these loci showed specificity in the target site sequence for Int-C3 mediated attL4X recombination. It can be further utilized to engineer Int variants for better recognition of this subset of attH4X sequence. To broaden the utility of the platform, the tool was further explored in the field of biologics testing and production. To achieve this, a master cell line of HEK293T was generated by random insertion of landing pads carrying 4X attH4X sequence with a reporter cassette. The landing pad of the master cell line was targeted with a seamless vector encoding a second reporter cassette. This resulted in the high reporter cassette expressing clones that harboured seamless vector in one of the four attH4X sequences of the landing pad. The master cell line was further utilized to integrate and express a large transgene of size ~14kb that encodes therapeutic factor VIII protein. The targeted bulk HEK293T showed a high expression of factor VIII protein with a yield of ~2.2µg/ml from 10000 cells indicating the potential application of this platform in the biopharmaceutical sector. Since this platform could allow integration of transgene(s) at a specific genomic locus, it can be further used to test different variants of a recombinant protein and select the best performing variant. In summary, a λ-integrase mediated seamless vector transgenesis platform was developed that manifests dual capability to generate seamless vectors as well as target the human genome for insertion and expression of large transgene cassette. This platform can be broadly utilized for various molecular medicine, gene therapy and synthetic biology applications.